PREVALENCE OF NUTRITIONAL DEFICIENCIES IN CRITICALLY ILL PATIENTS ADMITTED TO INTENSIVE CARE UNIT - T MURALI; JANANI; ARTHI; N SELVARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study was conducted to assess the incidence of the excisting malnutrition in critically ill patients who are admitted to ICU. So that this can help in improving the nutrition therapy in these critically ill patients. And, to identify the comorbidities which as associated with severe malnutrition. Methods: All patients who are above 18 years admitted to ICU irrespective of sex, diagnosis and severity of disease are assessed for nutritional status with SGA score within 24 hours of admission. Results: In males severe malnourishment was noted in elderly age group with mean age of 64.33 ±17.32 compared to patients with < 60 years. In female patients moderately nourished patients were older with mean age of 61.37±12.69. there is no difference between male and female in well-nourished and severely malnourished group. But in moderately nourished group females are more than males(32.09% vs 24.92%). Diabetes mellitus seem to be the most common comorbidity noted. In diabetes mellitus 81.39% of patients were severely malnourished. Conclusion: it is shown that most of the patients admitted to ICU presents with pre excisting malnutrition. So nutrition therapy plays import role in management of these patients.